2022
DOI: 10.1001/jamanetworkopen.2021.47042
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of COVID-19 Risk Following a Ring Vaccination Intervention to Address SARS-CoV-2 Alpha Variant Transmission in Montreal, Canada

Abstract: IMPORTANCEGiven limited COVID-19 vaccine availability early in the pandemic, optimizing immunization strategies was of paramount importance. Ring vaccination has been used successfully to control transmission of other airborne respiratory viruses. OBJECTIVE To assess the association of a ring vaccination intervention on COVID-19 spread in the initial epicenter of SARS-CoV-2 Alpha variant transmission in Montreal, Canada. DESIGN, SETTING, AND PARTICIPANTS This cohort study compared COVID-19 daily disease risk i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…43 However, a trial of ring vaccination against the Alpha variant demonstrated reduced risk of contracting COVID-19 in areas with high local transmission. 47 …”
Section: Discussionmentioning
confidence: 99%
“…43 However, a trial of ring vaccination against the Alpha variant demonstrated reduced risk of contracting COVID-19 in areas with high local transmission. 47 …”
Section: Discussionmentioning
confidence: 99%
“…Vaccine boosters have been found to increase antibody titers in those with poor responses to primary vaccination, but virus neutralizing titers remain suboptimal in the majority of patients after a third or fourth dose, and a subgroup of patients remain seronegative ( 1012 ). Indirect approaches to protect KTRs through ring vaccination may be beneficial in the immediate-term ( 13 ), however a strategy to directly boost immunity in immunosuppressed individuals is urgently needed ( 14 ). Such a strategy would likely center on transient modification of immunosuppression, and must strike the balance of enhancing vaccine immunogenicity and efficacy without increasing the risk of transplant rejection.…”
Section: Introductionmentioning
confidence: 99%
“…Limited research has been conducted comparing the additive mitigating effects of prevention and control measures among major provinces in Canada. With the exception of a few studies focused mainly on COVID-19 vaccine effectiveness, little research has examined the effects of initiating public health interventions or the emergence of new variants on COVID-19 transmission potential and disease burden in Canada ( 8 , 9 ). Moreover, differences in time-varying reproduction number (R t ) and incidence rate ratio (IRR) associated with specific SARS-CoV-2 variants have yet to be explored among populations in Canada.…”
mentioning
confidence: 99%